Tendência de mortalidade de idosos por doenças crônicas no município de Marília-SP, Brasil: 1998 a 2000 e 2005 a 2007 - Carvalho, Maria Helena Ribeiro de; Carvalho, Sebastião Marcos Ribeiro de [UNESP]; Laurenti, Ruy; Payão, Spencer Luiz Marques (Secretaria de Vigilância em Saúde - Ministério da Saúde do Brasil, 2014)
OBJECTIVE: to describe elderly mortality from cardiovascular and respiratory diseases and neoplasms in Marilia (SP). METHODS: this is a descriptive study of mortality from three diseases as defined by the 10th International Classification of Diseases, between 1998-2000 and 2005-2007. Mortality Information System records were used. Mortality rates by age and sex were calculated. RESULTS: circulatory diseases were the main causes of death among the elderly (39.25%). Neoplasm decline was noticed in both sexes and in those aged 60-69, particularly prostate cancer in men (-83.86%) and breast cancer (-70.96%) in this age group. Deaths from respiratory diseases increased in patients aged 80 and older: 39.31% in men and 57.92% in women. CONCLUSION: mortality from circulatory diseases and neoplasms among the elderly showed a decline, with increased mortality from respiratory system problems in patients 80 years of age and older.

OBJETIVO: descrever a mortalidade de idosos por doenças cardiovasculares, respiratórias e neoplasias no município de Marília-SP, Brasil. MÉTODOS: estudo descritivo da mortalidade pelos grupos de três doenças segundo a Décima Revisão da Classificação Estatística Internacional de Doenças e Problemas Relacionados à Saúde (CID-10), nos períodos 1998-2000 e 2005-2007; utilizaram-se registros do Sistema de Informações sobre Mortalidade (Sim) e calcularam-se os coeficientes de mortalidade por idade e sexo. RESULTADOS: doenças do aparelho circulatório lideraram as causas de mortalidade dos idosos (39,25%); houve declínio da mortalidade por neoplasias em ambos os sexos e na faixa etária de 60-69 anos, câncer da próstata nos homens (-83,36%) e de mama nas mulheres (-70,96%); óbitos por doenças do aparelho respiratório aumentaram aos 80 e mais anos, em homens (+39,31%) e mulheres (+57,92%). CONCLUSÃO: a mortalidade dos idosos por doenças cardiovasculares e neoplasias apresentou declínio, enquanto aumentou por doenças respiratórias na faixa etária ≥80 anos.
Chronic disease-related elderly mortality trends in the city of Marilia-SP, Brazil: 1998-2000 and 2005-2007
Keywords: Doença Crônica; Mortalidade; Saúde do Idoso; Chronic Disease; Mortality; Health of the Elderly